Lithuanian Catechism for Rural Schools (1795). Circumstances of its Compilation - Sidabraitė, Žavinta (Knygotyra, 2021)
Researchers constantly add new items to the bibliography of Lithuanian publications published in East Prussia in the last decade of the 18th century. The initiatives of publishing in local languages of that period were driven by the reforms of the Church and schools carried out by the Prussian authorities while the Enlightenment was coming to an end and the ideology of regional particularism was continuously growing in the country. As can be seen from newly discovered archival documents and already recorded bibliographic information, at least four publications dedicated for primary Christian education were published in Prussia in 1795, namely, the New Testament, the psalm book, the semi-secular reading textbook The Friend of Children (Kūdikių prietelius), and the catechism for rural schools. The editions of the New Testament and Kūdikių prietelius are recorded in the Lithuanian bibliography, however, nothing has been known about the mentioned editions of the psalm book and the catechism so far. The circumstances of their publishing are analysed in the article.